Gestational disruptions in metabolic rhythmicity of the liver, muscle, and placenta affect fetal size. Issue 4 (12th January 2017) - Papacleovoulou, Georgia; Nikolova, Vanya; Oduwole, Olayiwola; Chambers, Jenny; Vazquez‐Lopez, Marta; Jansen, Eugene; Nicolaides, Kypros; Parker, Malcolm; Williamson, Catherine
Abstract : Maternal metabolic adaptations are essential for successful pregnancy outcomes. We investigated how metabolic gestational processes are coordinated, whether there is a functional link with internal clocks, and whether disruptions are related to metabolic abnormalities in pregnancy, by studying day/night metabolic pathways in murine models and samples from pregnant women with normally grown and large‐for‐gestational age infants. In early mouse pregnancy, expression of hepatic lipogenic genes was up‐regulated and uncoupled from the hepatic clock. In late mouse pregnancy, rhythmicity of energy metabolism‐related genes in the muscle followed the patterns of internal clock genes in this tissue, and coincided with enhanced lipid transporter expression in the fetoplacental unit. Diurnal triglyceride patterns were disrupted in human placentas from pregnancies with large‐for‐gestational age infants and this overlapped with an increase in BMAL1 expression. Metabolic adaptations in early pregnancy are uncoupled from the circadian clock, whereas in late pregnancy, energy availability is mediated by coordinated muscle‐placenta metabolic adjustments linked to internal clocks. Placental triglyceride oscillations in the third trimester of human pregnancy are lost in large‐for‐gestational age infants and may be regulated by BMAL1. In summary, disruptions in metabolic and circadian rhythmicity are associated with increased fetal size, with implications for the pathogenesis of macrosomia. —Papacleovoulou, G., Nikolova, V., Oduwole, O., Chambers, J., Vazquez‐Lopez, M., Jansen, E., Nicolaides, K., Parker, M., Williamson, C. Gestational disruptions in metabolic rhythmicity of the liver, muscle, and placenta affect fetal size. FASEB J . 31, 1698–1708 (2017) www.fasebj.org